Porous TaCx ISOL target materials from mould-casted Ta4AlC3 - Griseri, Matteo; Biggemann, Jonas; Ramos, João Pedro; Li, Guichuan; Dams, Ot; Popescu, Lucia; Vleugels, Jozef; Fey, Tobias; Lambrinou, Konstantina (Journal of the European Ceramic Society, 2021)
Mould casting and sacrificial templating techniques, common in bioceramic technology, were employed to process porous TaCx ultra-high temperature ceramics intended as novel target materials for isotope separation on-line (ISOL) facilities, aiming primarily at the production of medical radioisotopes. A feedstock of Ta4AlC3 MAX phase powder, polyamide spheres and wax was used to obtain different porous TaCx grades with bimodal pore size distributions. The ‘green’ bodies underwent de-binding and vacuum annealing to decompose the MAX phase, whereas a reference material was also produced from commercial TaC powders. The thermal stability of the porous TaCx ceramics was assessed at ISOL-relevant conditions by heating in high vacuum up to 2200 °C. The MAX phase-derived TaCx porous ceramics evolved from biphasic TaCx/α-Ta2C to single-phase TaCx at higher temperatures, due to carbon incorporation. The porous TaCx microstructure was stable at 2200 °C with a specific surface area stabilizing at ∼0.25 m2/g and thermal conductivity of 1−4 W/m K.
Created from Fastlane, Scopus look-up
Keywords: ISOL target materials; Mould casting; Porous ultrahigh temperature ceramics; Ta; TaC